2019
DOI: 10.1186/s13023-019-1111-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel genotypes and phenotypes among Chinese patients with Floating-Harbor syndrome

Abstract: Background Floating-Harbor syndrome (FHS) is a rare syndromic short stature disorder caused by truncating variants in SRCAP . Few Chinese FHS patients had been reported so far and limited knowledge regarding the benefit of growth hormone treatment existed. Methods We ascertained 12 short stature patients with molecularly confirmed diagnosis of FHS by whole exome sequencing. We performed a comprehensive clinical evaluation for all patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
(49 reference statements)
2
22
0
4
Order By: Relevance
“…The dominant-negative effect of the truncated protein variant encoded by the SRCAP gene is FHS (14). Currently, more than 40 pathogenic variants of the SRCAP gene associated with FHS have been reported (mainly nonsense or frameshift mutations in exon 34), and most of these mutations occur between codons 2407 and 2517, while only two variants are nonsense mutations in exon 33. c.7330C>T (p.Arg2444Ter) is the most common variant, while c.7303C>T (p.Arg2435Ter) is the second most common variant (2). The heterozygous mutation (c.7401delC; p.Ile2468Phefs * 7) in the SRCAP gene of our patient was a de novo frameshift mutation in exon 34, with the mutation site located between codons 2407 and 2517, which is consistent with the previous description.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The dominant-negative effect of the truncated protein variant encoded by the SRCAP gene is FHS (14). Currently, more than 40 pathogenic variants of the SRCAP gene associated with FHS have been reported (mainly nonsense or frameshift mutations in exon 34), and most of these mutations occur between codons 2407 and 2517, while only two variants are nonsense mutations in exon 33. c.7330C>T (p.Arg2444Ter) is the most common variant, while c.7303C>T (p.Arg2435Ter) is the second most common variant (2). The heterozygous mutation (c.7401delC; p.Ile2468Phefs * 7) in the SRCAP gene of our patient was a de novo frameshift mutation in exon 34, with the mutation site located between codons 2407 and 2517, which is consistent with the previous description.…”
Section: Discussionsupporting
confidence: 91%
“…The SRCAP gene is located on chromosome 16p11.2, which contains a 40,989-bp coding region and 34 exons encoding a SNF2-related chromatin remodeling ATPase (the SRCAP protein), which is abundant in the nuclei of human cells (2). The SRCAP protein plays a crucial role in essential cellular pathways, such as chromatin remodeling, gene expression, DNA damage response, and cell division (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garcia et al [ 13 ] suggested that FHS may lead to impaired IGF-1 signaling because of the discrepancy between the modest growth response to GH therapy and serum IGF-1 level (upper limit of the normal level during therapy). To date, over 100 FHS cases have been reported worldwide, and only a few of these patients were GH deficient [ 8 , 14 ]. Table 2 summarizes the results of previous studies on GH therapy in FHS patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 100 FHS cases have been reported worldwide, and only a few of these patients were GH deficient. 8,14) Table 2 summarizes the results of previous studies on GH therapy in FHS patients. According to these studies, the modalities of GH therapy, age of onset, dose, treatment period, and results have been inconsistent.…”
Section: Table 2 a Summary Of Case Reports Of Floating-harbor Syndromentioning
confidence: 99%